Perancangan kursi sustainable yang berbasis budaya Nusantara di Pelabuhan Surabaya North Quay - Ferel Gunawan (Institut Seni Indonesia Yogyakarta, 2022)
The design of this chair originated from the problems that exist in the waiting room of the Surabaya North Quay port where there are still many interior product designs for standard public spaces, so that it seems boring and uncomfortable to use for a long time, therefore an innovation has emerged to create. comfortable chairs used for a long time with the concept of lesehan culture which is a sitting culture that was passed down by our ancestors and we should maintain this distinctive feature of Indonesian sitting culture in the midst of an increasingly modern era. The design is designed so that the user can sit cross-legged and stretch out comfortably, therefore the seat is made wide with a reference to sitting cross-legged and long as a reference for sitting side-by-side so that the user can determine the sitting position that is most comfortable because it is different from western sitting culture which prioritizes ergonomics. Indonesians feel more comfortable when given the freedom to achieve the relaxation they desire. The main principle of sustainability that the writer wants to apply here by utilizing used material which is wasted into a pile of garbage can be a valuable product.